Promoting equitable and high-quality STEM education in China from an ecological perspective - Yu Peng; Fangfang Zhao; Yonghe Zheng (Disciplinary and Interdisciplinary Science Education Research)
Abstract Drastic environmental and social changes have driven the global urgency to improve science, technology, engineering, and mathematics (STEM) education. However, the understanding of the elements within STEM education and how they interact with each other remains limited. In response to the challenges in promoting equitable and quality STEM education, we call for the application of an ecological perspective to STEM education based on Bronfenbrenner’s ecological systems theory. This STEM education ecosystem includes the core goal of preparing the next generation’s STEM literacy for future life and work, and the four subsystems that impact individuals’ development of STEM literacy. The elements and their roles across the micro-, exo-, macro-, and chrono-systems are elaborated. Examples of STEM education practices in China are described and analyzed to illustrate how the elements interact within and across subsystems. The implications of using the ecological perspective to provide equitable and high-quality STEM learning opportunities for diverse learners are discussed.